The Efficacy of Lavender Aromatherapy in Reducing Preoperative Anxiety in Ambulatory Surgery Patients Undergoing Procedures in General Otolaryngology. Issue 6 (8th November 2017) - Wotman, Michael; Levinger, Joshua; Leung, Lillian; Kallush, Aron; Mauer, Elizabeth; Kacker, Ashutosh
Abstract : Background: Preoperative anxiety is a common problem in hospitals and other health care centers. This emotional state has been shown to negatively impact patient satisfaction and outcomes. Aromatherapy, the therapeutic use of essential oils extracted from aromatic plants, may offer a simple, low‐risk and cost‐effective method of managing preoperative anxiety. The purpose of this study was to evaluate the efficacy of lavender aromatherapy in reducing preoperative anxiety in ambulatory surgery patients undergoing procedures in general otolaryngology. Methods: A prospective and controlled pilot study was conducted with 100 patients who were admitted to New York‐Presbyterian/Weill Cornell Medical Center for ambulatory surgery from January of 2015 to August of 2015. The subjects were allocated to two groups; the experimental group received inhalation lavender aromatherapy in the preoperative waiting area while the control group received standard nursing care. Both groups reported their anxiety with a visual analog scale (VAS) upon arriving to the preoperative waiting area and upon departure to the operating room. Results: According to a Welch's two sample t‐test, the mean reduction in anxiety was statistically greater in the experimental group than the control group ( p  = 0.001). Conclusion: Lavender aromatherapy reduced preoperative anxiety in ambulatory surgery patients. This effect was modest and possibly statistically significant. Future research is needed to confirm the clinical efficacy of lavender aromatherapy. Level of Evidence: 2b